Host Perspectives of High-Income Country Orthopaedic Resident Rotations in Low and Middle-Income Countries. (21st September 2022) - Roberts, Heather J.; Coss, Nathan; Urva, Mayur; Haonga, Billy; Woolley, Pierre-Marie; Banskota, Bibek; Morshed, Saam; Shearer, David W.; Sabharwal, Sanjeev
Abstract : Background: International orthopaedic resident rotations in low and middle-income countries (LMICs) are gaining popularity among high-income country (HIC) residency programs. While evidence demonstrates a benefit for the visiting residents, few studies have evaluated the impact of such rotations on the orthopaedic surgeons and trainees in LMICs. The purpose of this study was to further explore themes identified in a previous survey study regarding the local impact of visiting HIC resident rotations. Methods: Using a semistructured interview guide, LMIC surgeons and trainees who had hosted HIC orthopaedic residents within the previous 10 years were interviewed until thematic saturation was reached. Results: Twenty attending and resident orthopaedic surgeons from 8 LMICs were interviewed. Positive and negative effects of the visiting residents on clinical care, education, interpersonal relationships, and resource availability were identified. Seven recommendations for visiting resident rotations were highlighted, including a 1 to 2-month rotation length; visiting residents at the senior training level; site-specific prerotation orientation with an emphasis on resident attitudes, including the need for humility; creation of bidirectional opportunities; partnering with institutions with local training programs; and fostering mutually beneficial sustained relationships. Conclusions: This study explores the perspectives of those who host visiting residents, a viewpoint that is underrepresented in the literature. Future research regarding HIC orthopaedic resident rotations in LMICs should include the perspectives of local surgeons and trainees to strive for mutually beneficial experiences to further strengthen and sustain such academic partnerships.